The Metaphors of Islamic Sciences Faculty Students on the Concepts of "Sultanate and the Republic - Murat Çalışoğlu (Anı Publishing, 2019)
The purpose of this study is to examine the thoughts of the students from Faculty of Islamic Sciences through the metaphors they developed about the sultanate and the republic. As a result of the literature review, it was found that no study was conducted related to these concepts. The study, in this regard, is important in contributing to the literature and to shed light on subsequent studies. This research was carried out with a phenomenology approach which is one of the qualitative research methods. In line with the objectives of the study, the protocols including open-ended questions which were applied on 105 participants, 65 females and 40 males, selected with criterion sampling method among the undergraduate students from the Faculty of Islamic Sciences in a Turkish State University in 2017-2018 academic years were analyzed with content analysis. As a result of the study, 105 metaphors, 90 of which were different, were identified related to the concept of republic. These metaphors are grouped in five themes: human (62), nature (23), vehicle (16), religion (2), concept (2). 102 metaphors, 83 of which were different, were identified related to the concept of Sultanate. These metaphors are grouped in six themes: management (32), vehicle (20), human (18), nature (16), sense (15), history (1).